The Shadow Economy is Retreating: The Example of Georgia - Kbiladze, David; Metreveli, Shorena (Ekonomika, 2016)
The economy of Georgia had corruptive characteristics at the end of the last century and that has largely contributed to the existence of high-scaled shadow economy. Tax avoidance by entrepreneurs is onsidered to be the main cause of shadow economy (Gabidzashvili, Kbiladze, 2010). The methodological measurement and assessment of the shadow economy is characterized by certain peculiarities; therefore, we have aimed to examine and assess the scale of shadow economy and its impact on the overall economy of Georgia. The research shows several di_erences between real indicators, obtained by interviewers using hidden chronometry, and those indicators declared by entrepreneurs (the non-traditional method of research). The differences reveal unregistered micro-level economy, and provide the basis for determining the scale of shadow economy on the macroeconomic level. This problem was discussed several times by the president of Georgia. The research uses methods of average values, time series and the correlation-regression analysis of data. The study allowed us to identify the pattern of shadow economy reduction in Georgia during recent years and its shifting from the illegal to legal sectors, also, the maintenance of same trends before 2020.